Mapping Consumer Usage Decisions in E-Commerce Platforms: A Literature Review of Brand Image and Electronic Word of Mouth in Shopee - Canberra Chelciliana Poetranto; Ayuningtyas Yuli Hapsari (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The rapid advancement of digital technology has fundamentally transformed consumer behaviour within e-commerce ecosystems, particularly regarding the adoption of mobile-based shopping platforms. Despite growing scholarly interest, the combined influence of brand image and electronic word of mouth (eWOM) on platform-specific usage decisions remains insufficiently synthesized in the existing literature. This study aims to map and analyze the roles of brand image and eWOM in shaping consumer decisions to use Shopee, one of Southeast Asia's most dominant e-commerce platforms. Employing a literature review methodology, this research identifies, evaluates, and critically synthesizes empirical and conceptual studies published in reputable national and international journals indexed in Scopus, Web of Science, and Sinta. A total of 42 peer-reviewed articles published between 2020 and 2025 were included in the final corpus. The findings reveal that brand image exerts a significant positive effect on consumer usage decisions, whereby a strong, credible, and consistent brand perception substantially elevates consumer trust and platform adoption intent. Concurrently, eWOM—operationalized through online reviews, star ratings, and peer recommendations disseminated via digital channels—demonstrates a robust and measurable impact on consumer decision-making by reducing perceived risk and amplifying purchase confidence. Notably, the synergistic interaction between brand image and eWOM produces a compounding effect on consumers' sustained intention to select and continuously engage with Shopee as their primary shopping platform. A key novel finding of this review is that eWOM does not merely act as a parallel influence alongside brand image; rather, it functions as a dynamic antecedent that actively shapes and reinforces brand image formation over time, creating a self-reinforcing cycle of positive consumer influence. These findings advance digital marketing theory by integrating brand equity and information adoption frameworks within the e-commerce context, while offering actionable strategic implications for platform managers in optimizing brand communication and user-generated content ecosystems.